Tantalising tongues: male carpet pythons use chemoreception to differentiate among females - Bryant, G.; Bateman, Bill; Fleming, P. (CSIRO Publishing, 2011)
For animals sparsely distributed across a landscape, finding and identifying a receptive female during a short breeding period can be a challenge for males. Many snakes appear to rely on the production of sex-specific pheromones to synchronise the timing of reproductive behaviour. The rare Australian south-west carpet python (Morelia spilota imbricata) displays non-aggressive mating aggregations of up to six males around a receptive female, suggesting that males are responding to some chemical signal that enables multiple males simultaneously to identify and locate the female. We investigated chemoreceptive response (tongue-flicking) of 10 male pythons under laboratory conditions to 12 (randomly ordered) treatments each presented for three minutes. Cutaneous chemicals (dissolved in hexane solvent) were collected on cotton buds from the skin of six female pythons and male responses to these were compared with six control treatments. Male pythons produced a greater number of tongue flicks during the first minute of each trial, with fewer in minutes 2 and 3. Male chemoreceptive response in the third minute varied significantly between treatments and was only maintained for trials presenting cutaneous chemicals collected from the three relatively largest female pythons. This experiment suggests that male carpet pythons can use chemoreception to obtain information about their social environment, identifying pheromone cues from large, potentially fecund females. This ability would be adaptive for male mate-selection behaviour and is likely to also reduce costs of searching behaviour.